Early Results from GLASS-JWST. XI. Stellar Masses and Mass-to-light Ratio of z > 7 Galaxies - P. Santini; A. Fontana; M. Castellano; N. Leethochawalit; M. Trenti; T. Treu; D. Belfiori; S. Birrer; A. Bonchi; E. Merlin; C. Mason; T. Morishita; et al. (The Astrophysical Journal Letters, 2023)
We exploit James Webb Space Telescope (JWST) NIRCam observations from the GLASS-JWST-Early Release Science program to investigate galaxy stellar masses at z > 7. We first show that JWST observations reduce the uncertainties on the stellar mass by a factor of at least 5–10, when compared with the highest-quality data sets available to date. We then study the UV mass-to-light ratio, finding that galaxies exhibit a a two orders of magnitude range of M / L _UV values for a given luminosity, indicative of a broad variety of physical conditions and star formation histories. As a consequence, previous estimates of the cosmic stellar-mass density—based on an average correlation between UV luminosity and stellar mass—can be biased by as much as a factor of ∼6. Our first exploration demonstrates that JWST represents a new era in our understanding of stellar masses at z > 7 and, therefore, of the growth of galaxies prior to cosmic reionization.